EGFR-mediated activation of adipose tissue macrophages promotes obesity and insulin resistance - Shirong Cao; Yu Pan; Jiaqi Tang; Andrew S. Terker; Juan Pablo Arroyo Ornelas; Guan-nan Jin; Yinqiu Wang; Aolei Niu; Xiaofeng Fan; Suwan Wang; Raymond C. Harris; Ming-Zhi Zhang (Nature Communications, 2022)
In obesity, adipose tissue is chronically inflamed, leading to insulin resistance, and adipose tissue macrophages (ATMs) are a major source of cytokines that aggravate adipocyte dysfunction. Here, the authors show that selective deletion of the epidermal growth factor receptor in ATMs decreased obesity and development of insulin resistance.